The effectiveness of the Shotloc training tool on basketball free throw performance and technique - Alexander, M. J. L.; Hayward-Ellis, J. (International Journal of Kinesiology & Sports Science, 2016)
Background: Shooting technique in young players is dependent on the correct positioning of the hand on the ball during release. The ShotLoc was designed to produce the optimal hand position on the ball for shooting accuracy and correct release. Purpose: The purpose of this study was to determine the effectiveness of the ShotLoc shooting device in improving the shooting technique of young elite basketball players. Method: Eighty male and female adolescent basketball players recruited from an Elite Player Development Program were videotaped shooting three free throws and then scored on the number of free throw shots made out of thirty. A number of kinematic shooting variables were measured from the video tape. All participants participated in four 20 minute shooting practice sessions on a once per week basis; the experimental group wore the ShotLoc training tool for all of these practices while the control group practiced normally. All players were then videotaped and scored on the number of free throw shots again. Results: Statistical analysis of free throw percentage showed a 6.6% increase in those participants who were trained with the ShotLoc, while the control group experienced a .6% decrease in shooting percentage. None of the kinematic variables were found to be significantly different between groups, except wrist flexion that increased in the control group following the intervention. Conclusion: the ShotLoc shooting aid could improve free throw shooting percentage following practice using the device.